Dampak Kenaikan Harga Bahan Bakar Minyak (BBM) terhadap Biaya dan Pendapatan Usaha Tani Sayuran - Suslinawati Suslinawati (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2013)
The increase in fuel affect production costs and revenues Article aims to analyze the impact of price increases on the cost of vegetables and farm income. The results showed explicit costs increased due to higher fuel prices. Plant mustard greens and spinach and profits decline Plant mustard greens and spinach and profits decline. Yet kale and cucumber plants have increased profits due to the increase in output prices This means that both types of vegetables because it is not affected by any increase in the price of its output.